PEMEROLEHAN KALIMAT BAHASA INDONESIA ANAK PRASEKOLAH USIA 5—6 TAHUN - Wahyuni, Sinta (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2023)
This article was written to (1) describe declarative sentence patterns for preschoolers aged 5-6 years. (2) describe the declarative imperative sentence patterns of preschool children aged 5-6 years. (3) to describe interrogative sentence patterns for preschool children aged 5-6 years. The source of this data is the speech of preschool children aged 5-6 years. Data were obtained using the observing method and supported by observation and recording techniques. The data obtained was transcribed into written language, identified, classified, and then conclusions were made. The findings of this research are the types of sentences and sentence patterns reviewed first from the declarative sentence forms of preschool children aged 5-6 years with patterns of reporting/providing information totaling 16 data. Second, imperative sentence forms of preschool children aged 5-6 years with ordering patterns total 14 data. Third, the form of interrogative sentences for preschool children aged 5-6 years with a barnya pattern totals 46 data